Legal Protection for the Sustainability of Traditional Markets Against the Development of Modern Retail in Parepare City - Safah, Nur Ainun; Rasyid, Wahyu Rasyid; Rahma, Wanda (Journal of Law Justice (JLJ), 2025)
This study aims to analyze the impact of modern retail on the sustainability of traditional markets in Parepare City, focusing on economic and social aspects. The study method used is a normative-empirical approach, which combines legal analysis of government policies and direct observation of policy implementation. The research location is focused on the Lakessi Traditional Market in Parepare City, with the research subjects being traditional market vendors and modern retailers. Data collection techniques include interviews, literature review, direct observation, and documentation, with descriptive-qualitative analysis to describe the existing phenomena. The novelty of this study lies in its focus on traditional market protection policies in Parepare City, which involves analyzing the implementation of the latest regulations related to business licensing restrictions and zoning, as well as the role of local government in strengthening traditional markets through empowerment and revitalization programs. The results show that the presence of modern retail has had a significant impact on traditional markets, particularly in terms of a decline in small traders' income. Before the development of modern retail, the average daily income of traditional market traders reached IDR 6,000,000, but after the development of modern retail, this figure decreased by about 20% to IDR 4,000,000 per day. Nevertheless, the Parepare City government has implemented various regulations to maintain a balance between traditional markets and modern retail, such as distance restrictions, business permit restrictions, and traditional market empowerment. In conclusion, although the development of modern retail has made a positive contribution to the regional economy, its impact on traditional markets is quite significant.